The Impact of Föhn Winds on Surface Energy Balance During the 2010–2011 Melt Season Over Larsen C Ice Shelf, Antarctica. Issue 22 (17th November 2017) - King, J. C.; Kirchgaessner, A.; Bevan, S.; Elvidge, A. D.; Kuipers Munneke, P.; Luckman, A.; Orr, A.; Renfrew, I. A.; van den Broeke, M. R.
Abstract: We use model data from the Antarctic Mesoscale Prediction System (AMPS), measurements from automatic weather stations and satellite observations to investigate the association between surface energy balance (SEB), surface melt, and the occurrence of föhn winds over Larsen C Ice Shelf (Antarctic Peninsula) over the period November 2010 to March 2011. Föhn conditions occurred for over 20% of the time during this period and are associated with increased air temperatures and decreased relative humidity (relative to nonföhn conditions) over the western part of the ice shelf. During föhn conditions, the downward turbulent flux of sensible heat and the downwelling shortwave radiation both increase. However, in AMPS, these warming tendencies are largely balanced by an increase in upward latent heat flux and a decrease in downwelling longwave radiation so the impact of föhn on the modeled net SEB is small. This balance is highly sensitive to the representation of surface energy fluxes in the model, and limited validation data suggest that AMPS may underestimate the sensitivity of SEB and melt to föhn. There is broad agreement on the spatial pattern of melt between the model and satellite observations but disagreement in the frequency with which melt occurs. Satellite observations indicate localized regions of persistent melt along the foot of the Antarctic Peninsula mountains which are not simulated by the model. Furthermore, melt is observed to persist in these regions during extended periods when föhn does not occur, suggesting that other factors may be important in controlling melt in these regions. Key Points: Föhn winds in the lee of the Antarctic Peninsula mountains and their impacts are captured in high‐resolution atmospheric model simulations and observations Significant changes in modeled components of the surface energy balance (SEB) occur during föhn The modeled response of net SEB and surface melt to föhn is not as strong as that seen in observations